Research on loss characteristics and current-carrying capacity of low-smoke halogen-free cables - Junmin Jing; Weicheng Xie; Changquan Song; Yefei Zhang; Huan Xie; Zehao Wang (AIP Advances, 2023)
The current-carrying capacity is one of the key factors that restrict the safe operation of cables. Accurately grasping the current-carrying capacity of cables is an important means to improve the efficiency and economic benefits of cable operation. The calculation standard of IEC60287 not only ignores the differences between different types of cables but also makes it difficult to make timely calculations and corrections according to the changes in cables during operation. Therefore, taking the WDZ-YJY3×16 cable as an example, the electromagnetic–thermal coupling simulation model is established and the finite element simulation analysis is carried out. First, the distribution characteristics of the cable core current are analyzed by establishing a good model for simulation calculations. Then, based on this, the imbalance of the three-phase current and the relationship between the core radius and sheath loss are studied. Finally, combined with the cross-sectional area of the cable core, the influence of the loss factor on the current-carrying capacity of WDZ (low-smoke halogen-free cables) is analyzed. The results show that when the cross-sectional area of the cable reaches 700 mm2, the relative error of the current-carrying capacity of the cable reaches about 9.1%. The calculation results lay a foundation for reasonably determining the current-carrying capacity of WDZ.